A New Criterion for the Vitality of Organs is the Junction Phenomenon of the Contralateral Arterial Flows - Zoltan Moishevich, Sigal; Olga Vladimirovn, Surnina (International Journal of Psychosocial Rehabilitation, 2020)
Relevance: The detected phenomenon of the junction of contralateral arterial flow is of particular importance for the creation of various blood flow models in necrosis and ischemic pathology, for the assessment of the vitality of organs in various operations, and for the prevention of necrosis, stitches and anastomoses failure, paresis, ischemic enteritis, and colitis.Target: Develop an effective clinical criterion for determining the viability of organs in surgical pathology during surgery and without surgery.Materials and method: A retrospective study was carried out (level of evidence"). 941 patients had a new criterion for organ viability based on a change in the spectrum of arterial arcs. All patients were divided into two groups: the first group with the viability of the organs (464 people) and the second group - patients with non-viable organs in various surgical pathologies (477 people).Conclusion: We proposed and developed a new clinical method for determining the viability of the small intestine without operational intervention. The gut is considered viable in the presence of contralateral intramural blood flow during ultrasound in mirror reflection. During the operation, a new clinical method for preventing the failure of intestinal stumps was developed by applying a purse-string suture in the junction of contralateral intramural vessels; at the same time, the threads of the purse-string suture are carried out over visible intramural vessels. The phenomenon of the junction of contralateral arterial flows proved to be effective in surgery and can also be used in other areas, for example, with drip irrigation.